Faktor-Faktor Yang Mempengaruhi Pelaku UMKM Memilih Pembiayaan iB Muamalat Modal Kerja Melalui Inklusi Keuangan Syariah - Huurun’iin, Huurun’iin; Ali HT, Herni; Meiria, Endah; Arafah, Santi (ITB AAS INDONESIA Surakarta, 2024)
This study aims to determine how influential financial experience, Islamic financial knowledge, and Islamic financial attitudes are on iB Muamalat Working Capital financing at PT. Bank Muamalat KCP Sumber through Islamic financial inclusion. The population and sample of this study are Micro, Small and Medium Enterprises that have recorded using iB Muamalat Working Capital financing at PT Bank Muamalat KCP Sumber which amounted to 96 customers. This study uses quantitative methods, namely data measured on a numerical scale, which is based on cross section data taken at one time with the use of data analysis in the form of SEM-PLS. The results of the research conducted with a confidence level of 95% based on sig. 5%, then the Islamic financial inclusion variable affects financial experience and Islamic financial knowledge, but Islamic financial inclusion does not affect Islamic financial attitudes. And the variables of financial experience, Islamic financial knowledge, Islamic financial attitudes affect iB Muamalat Working Capital financing based on sig value